Clinical feature of omicron infection in children with inborn errors of immunity in China - Yang, Han; Sun, Fei; He, Ziwei; Li, Yan; Lu, Dan; Han, Tongxin; Mao, Huawei (Frontiers in Immunology, 2024)
This cohort study retrospectively reviewed 71 SARS-CoV-2-infected children with IEI using nationwide data from the National Center for Children's Health of China. COVID-19 was diagnosed by a positive rapid antigen or nucleic acid test result. Among 71 SARS-CoV-2infected children with IEI, male preponderance (male: female ratio of ~1.8:1), a median age of 8 years , and a predominance of antibody deficiency (19/71, 26.8%) were detected. Most of the patients got infected through household transmission, while a small proportion of them did so during hospital visits. The mean time periods were 3.3 days (n=44) for incubation, 8.4 days for symptoms (n=69), and 8.8 days for viral shedding (n=37). The time to viral shedding was proportional to the symptomatic period (R 2 =0.1243, p=0.0323) and prolonged in children with X-linked agammaglobulinemia. The most common symptoms of COVID-19 were fever, and some children showed only aggravation of the underlying disease.15% of IEI children progress to pneumonia, 85% require medication, 17% are admitted to hospital, and 4.1% are classified as critical. Previously application of anti-infective medications was associated with an increased risk of hospitalization after COVID-19 infection. Of the 71 children with IEI, all recovered from COVID-19. Overall, Omicron variant did not cause significant life-threatening infections among children with IEI in China, and most of them had a good clinical outcome. Nevertheless, these children exhibit an increased vulnerability to higher hospitalization rates, pneumonia, and severe illness compared to the general pediatric population.